A microfluidic structure battery based on LOM process 3D printing and its preparation method

Through LOM 3D printing technology, the microfluidic skeleton and electrodes are manufactured in paper-based batteries, which solves the problem of poor fluidity of electrolyte liquid in traditional paper-based batteries, realizes efficient production of batteries and multiple utilization of electrolyte liquids, and extends the use of batteries. Lifespan and improve environmental protection and performance.

CN117790917BActive Publication Date: 2025-01-17ZMARTEC TECH(SHENZHEN) LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311858344.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-01-17
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

Traditional paper-based batteries cannot recharge after electrolyte consumption, resulting in low capacity, short battery life, poor fluidity of the electrolyte liquid inside the battery, and problems such as low stability, short service life, low energy density and power density.

Method used

Using LOM 3D printing technology to produce paper-based electrolyte microfluidic frameworks and electrodes, the microfluidic channel is formed through laser cutting and bonding, so as to realize interlayer flow and multiple utilization of electrolyte liquid, combined with conductive materials and switching switch design, extend the battery service life.

Benefits of technology

It realizes efficient production and customized design of the battery, improves the battery capacity and battery life, extends the battery life, reduces the battery waste, and improves environmental protection and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117790917B_ABST
    Figure CN117790917B_ABST
Patent Text Reader

Abstract

The present invention provides a microfluidic structure battery based on LOM process 3D printing and a preparation method thereof, belonging to the technical field of microfluidic structure batteries; the technical problem to be solved is: to provide an improvement of a microfluidic structure battery based on LOM process 3D printing and a preparation method thereof; the technical scheme adopted to solve the technical problem is: a microfluidic channel is printed inside a paper-based electrolyte microfluidic skeleton by LOM process 3D printing, the upper surface and the lower surface of the paper-based electrolyte microfluidic skeleton are respectively covered with a layer of conductive material, electrodes are arranged at both ends of the paper-based electrolyte microfluidic skeleton, and the electrodes are connected to an external circuit through wires; the paper-based electrolyte microfluidic skeleton is also filled with electrolyte liquid, and the electrolyte liquid is specifically injected from the position of the electrode by an injection pump; a switching switch for controlling the movement of the electrode is arranged on the battery housing, and the switching switch is connected to the conductive material on the surface of the paper-based electrolyte microfluidic skeleton; the present invention is applied to microfluidic structure batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention provides a microfluidic structure battery based on LOM process 3D printing and a preparation method thereof, belonging to the technical field of microfluidic structure batteries. Background Art

[0002] Paper-based batteries are batteries that use paper as a carrier and are filled with electrolytes. They have the advantages of low cost, light weight, easy handling and biodegradability, and are suitable for sensors, wearable devices, instant detection and diagnosis, and other fields. Currently, the paper-based batteries available on the market mainly include paper-based zinc-air batteries, paper-based lithium-air batteries, paper-based enzyme batteries, etc. However, traditional paper-based batteries cannot be recharged after the electrolyte is consumed, resulting in low capacity and short battery life. In addition, the fluidity of the electrolyte inside the battery is poor, and there are defects such as low battery stability, short battery life, and low battery energy density and power density.

[0003] In order to solve these problems, attempts are currently being made to introduce microfluidic technology into the production of paper-based batteries, that is, microfluidic channel structures can be used to control the delivery and distribution of electrolytes to improve the uniformity and efficiency of batteries. Microfluidic technology is a technology that uses micron or nanoscale fluid channels to achieve precise manipulation and operation of fluids. It has the characteristics of low sample consumption, high sensitivity, high integration, and high repeatability, and has been widely used in chemistry, biology, medicine and other fields.

[0004] However, there are still many technical barriers to applying microfluidic technology to paper-based batteries. Currently, photolithography, paraffin printing, laser cutting and other methods are used to make microfluidic channels on paper-based batteries, and paper stacking, paper folding, paper curling and other methods are used to form three-dimensional microfluidic structures on paper. However, these methods have some defects, such as complex production process, high cost, low resolution, poor reproducibility, etc. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, the present invention aims to solve the technical problem of providing a microfluidic structure battery based on LOM process 3D printing and an improvement in its preparation method.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a microfluidic structure battery based on LOM process 3D printing, including a three-layer paper-based electrolyte microfluidic skeleton 3D printed by LOM process, an upper, middle and lower structure formed by stacking each paper-based electrolyte microfluidic skeleton is encapsulated in a battery shell, a microfluidic channel is 3D printed inside the paper-based electrolyte microfluidic skeleton by LOM process, a layer of conductive material is respectively covered on the upper surface and the lower surface of the paper-based electrolyte microfluidic skeleton, electrodes are arranged at both ends of the paper-based electrolyte microfluidic skeleton, and the electrodes are connected to an external circuit through a wire;

[0007] The paper-based electrolyte microfluidic skeleton is also filled with electrolyte solution, and the electrolyte solution is specifically injected from the position of the electrode through a syringe pump;

[0008] A switching switch for controlling the movement of the electrode is also arranged on the battery housing, and the switching switch is connected to the conductive material on the surface of the paper-based electrolyte microfluidic skeleton.

[0009] The paper-based electrolyte microfluidic skeletons in the middle and lower layers are also provided with enhanced media for adsorbing and transferring ions in the electrolyte solution.

[0010] The microfluidic channel is specifically a tree-like channel connected by a plurality of branch points, and a regulating valve is provided at each branch point for controlling the flow rate and direction of the electrolyte solution.

[0011] A docking mechanism is also arranged around each paper-based electrolyte microfluidic skeleton. The docking mechanism is specifically a mortise and tenon structure arranged at the end of the paper-based electrolyte microfluidic skeleton, which can connect and fix the paper-based electrolyte microfluidic skeletons of adjacent layers.

[0012] The positive electrode of the electrode is specifically prepared from a mixed material of a heterocyclic polymer such as polyaniline, polypyrrole, polythiophene and lithium manganate;

[0013] The negative electrode of the electrode is specifically prepared from a mixed material of graphite, a conductive agent, a thickener, and a binder.

[0014] The electrolyte solution is specifically a polymer gel electrolyte, and the polymer gel electrolyte is specifically prepared by using polyethylene oxide as a polymer matrix and mixed with lithium manganese oxide to form a material.

[0015] The switching switch is specifically an electromagnetic switch composed of an electromagnet and a spring.

[0016] The conductive material is specifically silver paste or graphite paste with adjustable viscosity.

[0017] A method for preparing a microfluidic structure battery based on LOM process 3D printing includes the following preparation steps:

[0018] Step S1, cutting polymer fiber paper or polyester film into 10 cm×10 cm squares, a total of 9 sheets are required, numbered 1-9 in sequence;

[0019] Step S2, placing the papers numbered 1, 4, and 7 into the LOM 3D printer, and using laser to cut out branch network-type microfluidic channels;

[0020] Step S3, placing the papers numbered 2, 5, and 8 into the LOM 3D printer, and using a laser to cut circular holes, the positions of the holes corresponding to the branch points on the papers numbered 1, 4, and 7, for connecting the microfluidic channels of the upper and lower layers;

[0021] Step S4, placing the papers numbered 3, 6, and 9 into the LOM 3D printer, and using a laser to cut circular holes, the positions of which correspond to the holes on the papers numbered 2, 5, and 8, for connecting the microfluidic channels of the upper and lower layers;

[0022] Step S5, stacking the papers numbered 1, 2, and 3 together in order, and bonding them into a whole by using a LOM 3D printer to form an upper paper-based electrolyte microfluidic skeleton;

[0023] Step S6, stacking the papers numbered 4, 5, and 6 together in order, and bonding them into a whole by using a LOM 3D printer to form a paper-based electrolyte microfluidic skeleton in the middle layer;

[0024] Step S7, stack the papers numbered 7, 8, and 9 together in order, and bond them into a whole using a LOM 3D printer to form a paper-based electrolyte microfluidic skeleton of the lower layer;

[0025] Step S8, coating the upper surface and the lower surface of the paper-based electrolyte microfluidic skeleton of the upper layer, the middle layer, and the lower layer with a layer of conductive material, respectively, to form a positive terminal and a negative terminal;

[0026] Step S9, preparing an electrolyte solution: polyethylene oxide, lithium manganate, water, and a cross-linking agent are mixed in a circular manner for multiple times in a heavy first and light second order, and then the mass ratio is linearly adjusted each time according to the paper wetting strength, and water and a cross-linking agent are added and stirred evenly to form a uniform solution, and then the solution is placed in a vacuum drying oven, dried, gelled, and solidified to obtain a polymer gel electrolyte;

[0027] Step S10, assembling the battery: stacking and connecting the upper, middle and lower paper-based electrolyte microfluidic skeletons together to form a whole, and then contacting the positive electrode material and the negative electrode material with the two end surfaces of the paper-based electrolyte microfluidic skeleton respectively to form a battery unit, repeating this step to make three battery units in total, and then stacking the three battery units together to form a battery pack;

[0028] Step S11, setting a switch on one side of the battery pack and connecting it to the conductive material to control the movement of the positive and negative electrode materials.

[0029] The beneficial effects of the present invention compared with the prior art are as follows: the present invention uses LOM 3D printing technology to manufacture paper-based electrolyte microfluidic skeletons and electrodes. The printing method uses laser cutting and bonding to stack paper-based materials and electrode materials into the required shape and size, and at the same time cuts microfluidic channels in the paper-based material. It has the advantages of simple manufacturing process, low cost, high resolution, good reproducibility, etc., and can realize efficient manufacturing and customized design of paper-based batteries; the printed paper-based electrolyte microfluidic skeleton can realize the interlayer flow and multiple utilization of the electrolyte solution, and can extend the service life of the battery. When the electrolyte solution in the upper layer undergoes an oxidation-reduction reaction with the positive and negative electrodes, the generated electrons flow to the external circuit through the conductive material to generate current. At the same time, the ions in the electrolyte solution pass through the microfluidic channels of the paper-based electrolyte microfluidic skeleton, from top to bottom, and enter the unit batteries in the middle and lower layers in turn, and undergo further oxidation-reduction reactions with the corresponding positive and negative electrodes, thereby realizing the interlayer flow of the electrolyte solution and extending the battery life. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be further described below in conjunction with the accompanying drawings:

[0031] Figure 1 It is a schematic diagram of the structure of the microfluidic structure battery of the present invention;

[0032] Figure 2 This is an enlarged effect diagram of the paper-based electrolyte microfluidic skeleton of the present invention;

[0033] Figure 3 This is an enlarged effect diagram of the microfluidic channel of the present invention;

[0034] Figure 4 This is an enlarged effect diagram of the interior of the microfluidic channel of the present invention;

[0035] In the figure: 001 is a paper-based electrolyte microfluidic skeleton, 002 is a battery shell, 003 is a microfluidic channel, 004 is an electrode, 005 is an electrolyte solution, 006 is a switching switch, and 007 is an enhanced medium. DETAILED DESCRIPTION

[0036] like Figures 1 to 4As shown, the present invention provides a microfluidic battery based on LOM paper-based 3D printing, aiming to provide a paper-based battery with good performance and environmental protection characteristics. The battery uses a heterocyclic polymer as a positive electrode material and graphite as a negative electrode material. The battery is divided into an upper, middle and lower three-layer structure, which is spliced ​​with a mortise and tenon structure. The upper layer is provided with a microfluidic channel, and the electrolyte is a polymer gel electrolyte. When the upper layer electrolyte reacts, the control switch is pressed to move the positive and negative electrode materials to the middle layer structure. The middle layer reinforcement medium is polyester paper, which can enhance ion transport. After the middle layer reacts, the control switch is pressed again to move the positive and negative electrode materials to the middle layer structure. The design realizes the reuse of the positive and negative electrodes of the battery and prolongs the battery life.

[0037] The LOM process (LOM 3D printing technology) used in the present invention is also called laminated object manufacturing, and its full English name is Laminated Object Manufacturing. The LOM process uses thin sheet materials (such as paper, plastic film or composite material) as raw materials, and uses a laser cutting system to cut the inner and outer contours of the workpiece with paper coated with hot melt adhesive on the back according to the cross-sectional contour line data extracted by the computer. The LOM process is used to prepare a paper-based microfluidic battery that can realize the flow of electrolyte between layers, thereby realizing the reuse of the positive and negative electrodes of the battery, which can significantly improve the battery capacity and battery life. At the same time, the use of paper substrate is conducive to the environmentally friendly use of battery-controlled products.

[0038] The microfluidic structure battery provided by the present invention comprises a positive electrode, a negative electrode and a paper-based electrolyte microfluidic skeleton, wherein the positive electrode is a heterocyclic polymer such as polyaniline (PANI), polypyrrole (Ppy), polythiophene (PTh) and lithium manganate (LiMn 2 O 4 ) mixed material, the negative electrode is made of graphite, conductive agent, thickener, and binder, and the positive and negative electrodes are both LOM 3D printed metal powders; the paper-based electrolyte microfluidic skeleton is LOM 3D printed paper, and the upper and lower surfaces are respectively covered with a layer of conductive material to form the positive and negative terminals. The paper has multiple microfluidic channels inside to enhance the ion transport between electrolytes; the electrolyte liquid is a polymer gel electrolyte, and the gel electrolyte uses polyethylene oxide (PEO) as a polymer matrix and lithium manganese oxide (LiMn 2 O 4 ) is injected into the paper-based electrolyte microfluidic skeleton from the positive terminal through a syringe pump, and an electrochemical reaction occurs with the positive and negative electrodes to generate current; the present invention adopts lithium carbonate as the positive electrode material and graphite as the negative electrode material. These two materials have high conductivity and high catalysis, can effectively promote the redox reaction in the electrolyte solution, and improve the performance of the battery. At the same time, they also have the characteristics of low cost, low toxicity and high stability, which meet the environmental protection requirements of the battery.

[0039] The battery is composed of three identical unit cells stacked together, each of which contains a paper-based electrolyte microfluidic skeleton. The positive electrode and the negative electrode are in contact with the two end surfaces of the paper-based electrolyte microfluidic skeleton respectively. The three unit cells are connected by a mortise and tenon structure to enhance the stability of the structure. The battery is provided with a switching switch to control the movement of the positive and negative electrode materials. When the upper layer electrolyte reacts, the switching switch is pressed to move the positive and negative electrode materials along the conductive material to the middle layer structure. When the middle layer electrolyte reacts, the switching switch is pressed again to move the positive and negative electrode materials along the conductive material to the lower layer structure, thereby realizing the reuse of the positive and negative electrodes of the battery and extending the battery life.

[0040] When the battery starts working, the electrolyte is injected into the paper-based electrolyte microfluidic skeleton from the positive terminal through the injection pump, and an electrochemical reaction occurs with the positive and negative electrodes to generate current. At the same time, the ions in the electrolyte pass through the microfluidic channel of the paper-based electrolyte microfluidic skeleton, and enter the unit cells of the middle and lower layers from top to bottom in turn, and further electrochemical reactions occur with the switched positive and negative electrodes, thereby realizing the interlayer flow and multiple utilization of the electrolyte, and improving the capacity and endurance of the battery. Among them, the paper-based electrolyte microfluidic skeletons in the middle and lower layers are both provided with an enhanced medium, which is a porous material with high ionic conductivity and high specific surface area. The enhanced medium can effectively adsorb and transfer ions in the electrolyte, increase the voltage and current of the battery, and can also absorb impurities and moisture in the electrolyte liquid, reduce the internal resistance and corrosion of the battery, and improve the stability and safety of the battery. The impurities and moisture in the electrolyte liquid can reduce the internal resistance and corrosion of the battery, and improve the stability and safety of the battery.

[0041] The microfluidic channel of the present invention is in the shape of a branch network type, wherein the branch network type microfluidic channel is a tree-like channel connected by multiple branch points, and each branch point has an adjustable valve for controlling the flow and direction of the electrolyte, thereby achieving precise distribution and mixing of the electrolyte, and improving the uniformity and stability of the battery. The design inspiration of the branch network type microfluidic channel comes from trees in nature. The roots, stems and leaves of trees have similar branch structures, which can effectively transport water and nutrients and adapt to different environmental conditions. The branch network type microfluidic channel can realize the interlayer flow and multiple utilization of the electrolyte, improve the capacity and endurance of the battery, and also reduce the waste of the battery and improve the environmental protection of the battery; it can adjust the flow and direction of the electrolyte according to the working state and demand of the battery, optimize the performance of the battery, and improve the efficiency and reliability of the battery; it can achieve uniform distribution and mixing of the electrolyte, improve the uniformity and stability of the battery, reduce the internal resistance and polarization of the battery, and increase the voltage and current of the battery.

[0042] The switching switch provided in the present invention is an electromagnetic switch, which consists of an electromagnet and a spring. When the electromagnet is energized, the spring is compressed, the conductive material is pulled, and the positive and negative electrode materials move to the next layer structure. When the electromagnet is de-energized, the spring returns to its original state, the conductive material is released, and the positive and negative electrode materials stay in the current layer structure, thereby realizing sequential control of the positive and negative electrodes of the battery.

[0043] The paper-based electrolyte microfluidic skeleton provided by the present invention is prepared from polymer fiber paper or polyester film by LOM 3D printing technology. The technology utilizes laser cutting and bonding to stack paper-based materials into required shapes and sizes, and at the same time cuts microfluidic channels in the paper-based skeleton for transporting gel electrolytes. The battery formed by the skeleton can realize multiple utilization of the electrolyte solution, prolong the service life of the battery, and also reduce the battery waste, thereby improving the environmental friendliness of the battery. The mortise and tenon structure of the battery adopts a detachable design, which is convenient for disassembly and replacement of the battery, while also reducing the weight and volume of the battery, thereby improving the portability and adaptability of the battery. By providing an enhanced medium, the voltage and current of the battery are increased, and at the same time, impurities and moisture in the electrolyte solution can be absorbed, thereby reducing the internal resistance and corrosion of the battery, thereby improving the stability and safety of the battery.

[0044] Furthermore, the method for preparing a microfluidic structure battery provided by the present invention requires preparing a paper-based electrolyte microfluidic skeleton from polymer fiber paper or polyester film by LOM 3D printing technology. The technology uses laser cutting and bonding to stack the paper-based materials into a desired shape and size, and at the same time cuts a microfluidic channel in the paper-based material, and then coats a layer of conductive material on the upper and lower surfaces of the paper-based material to form a positive terminal and a negative terminal; the specific preparation steps are as follows:

[0045] Step S1, cutting polymer fiber paper or polyester film into 10 cm×10 cm squares, a total of 9 sheets are required, numbered 1-9 in sequence;

[0046] Step S2, placing the papers numbered 1, 4, and 7 into the LOM 3D printer, and using laser to cut out a branch network type microfluidic channel, wherein the spacing between the branch points is 1 mm, the width of the channel is 0.1 mm, the depth is 0.2 mm, and the total length of the channel is 9 cm;

[0047] Step S3, placing the papers numbered 2, 5, and 8 into the LOM 3D printer, and using a laser to cut circular holes with a diameter of 0.5 mm. The positions of the holes correspond to the branch points on the papers numbered 1, 4, and 7, and are used to connect the microfluidic channels of the upper and lower layers;

[0048] Step S4, placing the papers numbered 3, 6, and 9 into the LOM 3D printer, and using a laser to cut circular holes with a diameter of 0.5 mm. The positions of the holes correspond to the holes on the papers numbered 2, 5, and 8, and are used to connect the microfluidic channels of the upper and lower layers;

[0049] Step S5, stack the papers numbered 1, 2, and 3 together in order, and use the bonding function of the LOM 3D printer to bond them into a whole to form an upper paper-based electrolyte microfluidic skeleton;

[0050] Step S6, stack the papers numbered 4, 5, and 6 together in order, and use the bonding function of the LOM 3D printer to bond them into a whole to form a paper-based electrolyte microfluidic skeleton in the middle layer;

[0051] Step S7, stack the papers numbered 7, 8, and 9 together in order, and use the bonding function of the LOM 3D printer to bond them into a whole, so as to form a paper-based electrolyte microfluidic skeleton of the lower layer;

[0052] Step S8, coating the upper and lower surfaces of the paper-based electrolyte microfluidic skeletons of the upper, middle and lower layers with a layer of conductive material, such as silver paste or graphite paste, to form a positive terminal and a negative terminal, with a thickness of 0.1 mm and an area of ​​10 cm×10 cm;

[0053] Step S9, preparing an electrolyte solution: mixing polyethylene oxide: lithium manganate: water: cross-linking agent = 1:1:0.8:0.3 in a mass ratio of first heavy and then light and then quantitative for multiple cycles, and then adjusting the mass ratio linearly according to the paper wetting strength each time, adding appropriate amounts of water and cross-linking agent, stirring evenly to form a uniform solution, and then placing the solution in a vacuum drying oven, drying, gelling and curing to obtain a polymer gel electrolyte with a thickness of 0.5 mm and an area of ​​10 cm×10 cm;

[0054] Step S10, assembling the battery: connecting the upper, middle and lower paper-based electrolyte microfluidic skeletons together according to the mortise and tenon structure to form a whole, and then contacting the positive electrode material and the negative electrode material with the two end surfaces of the paper-based electrolyte microfluidic skeleton respectively to form a battery unit, repeating this step to make three battery units, and then stacking the three battery units together to form a battery pack;

[0055] Step S11, setting a switch on one side of the battery pack and connecting it to the conductive material to control the movement of the positive and negative electrode materials.

[0056] Test battery performance: connect the battery pack to an external circuit, inject electrolyte from the positive terminal through a syringe pump, observe changes in battery voltage and current, press the switch to change the position of the positive and negative electrode materials, observe the battery's usage time and number of cycles, and evaluate the battery's capacity, power, stability, and safety.

[0057] Example 1

[0058] This embodiment uses the following materials and equipment:

[0059] Polymer fiber paper: a paper-based material with high strength, high flexibility and high transparency, made by mixing polyvinyl alcohol (PVA) and cellulose ((C6H10O5)n) in a mass ratio of 1:1, spinning, drying and cutting, with a thickness of 0.2 mm and an area of ​​10 cm×10 cm;

[0060] Lithium carbonate: A commonly used positive electrode material, made of lithium carbonate (Li 2 CO 3 ) and conductive agent (acetylene black (AB)) were mixed in a mass ratio of 9:1, ball-milled, dried and sieved, and the particle size was 10 μm;

[0061] Graphite: A commonly used negative electrode material, which is made by mixing graphite (C), conductive agent (acetylene black (AB)), thickener (CMC) and binder (PVDF) in a mass ratio of 8:1:0.5:0.5, and then ball milling, drying and sieving. Its particle size is 10 μm;

[0062] Silver paste: A commonly used conductive material, which is made by mixing silver powder (Ag) and binder (PVA) in a mass ratio of 9:1, stirring, drying and grinding, with a particle size of 1 μm;

[0063] Polyethylene oxide (PEO): A commonly used polymer matrix, made by polymerization of ethylene oxide (EO), with a molecular weight of 10,000 g / mol;

[0064] Lithium manganate (LiMn 2 O 4 ): A commonly used electrolyte salt composed of lithium manganese oxide (LiMn 2 O 4 ) is refined and dried, with a purity of 99.9%;

[0065] Water (H 2 O): A commonly used solvent made from tap water by distillation and filtration, with a purity of 99.9%;

[0066] Cross-linking agent (EGDMA): A commonly used cross-linking agent, made from ethylene glycol dimethacrylate (EGDMA) after refining and drying, with a purity of 99.9%;

[0067] LOM 3D printer: a device that uses laser cutting and bonding to stack paper-based materials and electrode materials into the required shape and size. Its model is XYZ-100, its laser power is 100 W, and its adhesive is PVA;

[0068] Syringe pump: a device used to inject electrolyte solution, its model is ABC-10, and its flow rate is 10 ml / min;

[0069] Vacuum drying oven: a device used for drying, gelling and solidifying electrolyte liquid, its model is DEF-50, its temperature is 50 ℃, and its pressure is 0.1 MPa;

[0070] Electromagnet: A device used to control the movement of positive and negative electrode materials, its model is GHI-20, its voltage is 20V, and its current is 1A;

[0071] Spring: A device used to control the movement of positive and negative electrode materials, its model is JKL-10, and its elastic coefficient is 10N / m;

[0072] Battery Tester: A device used to test battery performance, its model is MNO-100, its voltage range is 0-5V, and its current range is 0-100 mA.

[0073] Example 2

[0074] Preparation of paper-based electrolyte microfluidic skeleton: The polymer fiber paper is prepared by LOM 3D printing technology. This technology uses laser cutting and bonding to stack the paper-based materials into the required shape and size, and cuts microfluidic channels in the paper-based materials. Then, a layer of silver paste is applied on the upper and lower surfaces of the paper-based materials to form the positive and negative terminals. The specific steps are as follows:

[0075] Cut the polymer fiber paper into 10cm x 10cm squares. A total of 9 sheets are needed, numbered 1-9 in sequence;

[0076] Put the papers numbered 1, 4, and 7 into the LOM 3D printer, and use laser to cut out a branch network type microfluidic channel, the spacing between the branch points is 1 mm, the width of the channel is 0.1 mm, the depth is 0.2 mm, and the total length of the channel is 9 cm;

[0077] Place the papers numbered 2, 5, and 8 into the LOM 3D printer and use a laser to cut circular holes with a diameter of 0.5 mm. The positions of the holes correspond to the branch points on the papers numbered 1, 4, and 7, which are used to connect the microfluidic channels of the upper and lower layers.

[0078] Put the papers numbered 3, 6, and 9 into the LOM 3D printer and use laser to cut circular holes with a diameter of 0.5 mm. The positions of the holes correspond to the holes on the papers numbered 2, 5, and 8, which are used to connect the microfluidic channels of the upper and lower layers.

[0079] Stack the papers numbered 1, 2, and 3 together in order, and use the bonding function of the LOM 3D printer to bond them into a whole to form the paper-based electrolyte microfluidic skeleton on the upper layer;

[0080] Stack the papers numbered 4, 5, and 6 together in order, and use the bonding function of the LOM 3D printer to bond them into a whole to form a paper-based electrolyte microfluidic skeleton in the middle layer;

[0081] Stack the papers numbered 7, 8, and 9 together in order, and use the bonding function of the LOM 3D printer to bond them into a whole to form the paper-based electrolyte microfluidic skeleton at the bottom layer;

[0082] The upper and lower surfaces of the paper-based electrolyte microfluidic skeletons of the upper, middle and lower layers are coated with a layer of silver paste to form positive and negative terminals, respectively, with a thickness of 0.1 mm and an area of ​​10 cm×10 cm.

[0083] Preparation of electrolyte solution: polyethylene oxide: lithium manganese oxide: water: cross-linking agent = 1:1:0.8:0.3 by mass ratio is mixed in a cycle of first heavy and then light and then quantitative, and then the mass ratio is linearly adjusted each time according to the paper wetting strength, and an appropriate amount of water and cross-linking agent EGDMA are added and stirred evenly to form a uniform solution, and then the solution is placed in a vacuum drying oven, dried, gelled and solidified to obtain a polymer gel electrolyte with a thickness of 0.5 mm and an area of ​​10 cm×10 cm.

[0084] Assemble the battery: connect the upper, middle and lower paper-based electrolyte microfluidic skeletons together according to the mortise and tenon structure to form a whole, and then contact the positive electrode material and the negative electrode material with the two end surfaces of the paper-based electrolyte microfluidic skeleton respectively to form a battery cell. Repeat this step to make three battery cells, and then stack the three battery cells together to form a battery pack and encapsulate them into a battery casing. Finally, set the switching switch on one side of the battery pack and connect it to the conductive material to control the movement of the positive and negative electrode materials.

[0085] Test battery performance: connect the battery pack to an external circuit, inject electrolyte from the positive terminal through a syringe pump, observe changes in battery voltage and current, press the switch to change the position of the positive and negative electrode materials, observe the battery's usage time and number of cycles, and evaluate the battery's capacity, power, stability, and safety.

[0086] The experimental data related to the battery performance measured in the embodiment of the present invention are: voltage 3.6V, current 50mA, capacity 180mAh, power 180mW, use time 3.6h, and number of cycles 10 times; it can be seen from the above data that the battery of this embodiment has higher voltage, current, capacity and power, and also has a longer use time and more cycles, which means that the battery of this embodiment has better performance and can meet some low power consumption, long life and environmental protection application requirements.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A microfluidic structure battery based on LOM process 3D printing, comprising a three-layer paper-based electrolyte microfluidic skeleton (001) 3D printed by LOM process, wherein the upper, middle and lower structures formed by stacking the paper-based electrolyte microfluidic skeletons (001) are encapsulated in a battery housing (002), characterized in that: A microfluidic channel (003) is 3D printed inside the paper-based electrolyte microfluidic skeleton (001) by LOM process, a layer of conductive material is respectively covered on the upper surface and the lower surface of the paper-based electrolyte microfluidic skeleton (001), and electrodes (004) are arranged at both ends of the paper-based electrolyte microfluidic skeleton (001), and the electrodes (004) are connected to an external circuit through a wire; The paper-based electrolyte microfluidic skeleton (001) is also filled with an electrolyte solution (005), and the electrolyte solution (005) is specifically injected from the position of the electrode (004) through a syringe pump; A switching switch (006) for controlling the movement of the electrode (004) is also provided on the battery housing (002), and the switching switch (006) is connected to the conductive material on the surface of the paper-based electrolyte microfluidic skeleton (001); The microfluidic channel (003) is specifically a tree-like channel connected by a plurality of branch points, and a regulating valve is provided at each branch point for controlling the flow rate and direction of the electrolyte solution (005).

2. According to claim 1, a microfluidic structure battery based on LOM process 3D printing is characterized in that: An enhanced medium (007) for adsorbing and transferring ions in the electrolyte solution is also arranged in the paper-based electrolyte microfluidic skeleton (001) in the middle layer and the lower layer.

3. According to claim 1, a microfluidic structure battery based on LOM process 3D printing is characterized in that: A docking mechanism is also provided around each paper-based electrolyte microfluidic skeleton (001), wherein the docking mechanism is specifically a mortise and tenon structure provided at the end of the paper-based electrolyte microfluidic skeleton (001), which can connect and fix adjacent layers of paper-based electrolyte microfluidic skeletons (001).

4. According to claim 1, a microfluidic structure battery based on LOM process 3D printing is characterized in that: The switching switch (006) is specifically an electromagnetic switch composed of an electromagnet and a spring.

5. According to claim 1, a microfluidic structure battery based on LOM process 3D printing is characterized in that: The conductive material is specifically silver paste or graphite paste with adjustable viscosity.

6. A method for preparing a microfluidic structure battery based on LOM process 3D printing, characterized in that: The method comprises the following preparation steps: Step S1, cutting polymer fiber paper or polyester film into 10 cm×10 cm squares, a total of 9 sheets are required, numbered 1-9 in sequence; Step S2, placing the papers numbered 1, 4, and 7 into the LOM 3D printer, and using laser to cut out a branch network type microfluidic channel (003); Step S3, placing the papers numbered 2, 5, and 8 into the LOM 3D printer, and using a laser to cut circular holes, the positions of which correspond to the branch points on the papers numbered 1, 4, and 7, for connecting the microfluidic channels (003) of the upper and lower layers; Step S4, placing the papers numbered 3, 6, and 9 into the LOM 3D printer, and using a laser to cut circular holes, the positions of which correspond to the holes on the papers numbered 2, 5, and 8, for connecting the microfluidic channels (003) of the upper and lower layers; Step S5, stacking the papers numbered 1, 2, and 3 together in order, and bonding them into a whole by using a LOM 3D printer to form an upper paper-based electrolyte microfluidic skeleton (001); Step S6, stacking the papers numbered 4, 5, and 6 together in order, and bonding them into a whole by using a LOM 3D printer to form a paper-based electrolyte microfluidic skeleton (001) in the middle layer; Step S7, stacking the papers numbered 7, 8, and 9 together in order, and bonding them into a whole by using a LOM 3D printer to form a paper-based electrolyte microfluidic skeleton (001) of the lower layer; Step S8, coating the upper surface and the lower surface of the paper-based electrolyte microfluidic skeleton (001) of the upper layer, the middle layer and the lower layer with a layer of conductive material respectively to form a positive terminal and a negative terminal; Step S9, preparing an electrolyte solution (005): polyethylene oxide, lithium carbonate, water, and a cross-linking agent are mixed in a circular manner for multiple times in a heavy first and light second order, and the weight ratio of each mixing is linearly adjusted according to the paper wetting strength, and water and a cross-linking agent are added and stirred evenly to form a uniform solution, and then the solution is placed in a vacuum drying oven, dried, gelled, and solidified to obtain a polymer gel electrolyte; Step S10, assembling the battery: stacking and connecting the upper, middle and lower paper-based electrolyte microfluidic skeletons (001) together to form a whole, and then contacting the positive electrode material and the negative electrode material with the two end surfaces of the paper-based electrolyte microfluidic skeleton (001) respectively to form a battery unit, repeating this step to make three battery units in total, and then stacking the three battery units together to form a battery pack; Step S11, setting a switch (006) on one side of the battery pack, connected to the conductive material, to control the movement of the positive and negative electrode materials.

Citation Information

Patent Citations

  • Method of making electrochemical reactor

    CN113302771A

  • Interconnect with Microchannels and Method of Making

    US20200144633A1